PENGARUH PROGRAM GERAKAN LITERASI SEKOLAH TERHADAP MINAT BACA PESERTA DIDIK - apriliyani, heryani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Literacy is one of the activities of reading can make an effort in the movement that is very important to educate life. One of them with literacy can gain widespread knowledge. High quality reading skills will affect the increase in students' reading interest. Interest in reading in all circles is still lacking, especially students and students who are struggling in the world of education. This is caused by people who are less aware of the benefits of literacy. The government makes a policy to build a culture of literacy through familiarizing students with reading before learning begins, namely the School Literacy Movement (GLS) program. This study intends to determine the effect of students on the ongoing learning process with the existence of the School Literacy Movement program on the reading fondness of students at SMP Negeri 1 Cisarua. The subjects in this study were students at SMP Negeri 1 Cisarua. The approach used in this study is a qualitative approach. Data collection techniques are done by questionnaire, observation, and documentation. The results of this study determine that the influence of the school literacy movement program can be beneficial in the learning process. Students' fondness for reading can increase after the Literacy Movement. School. Literacy culture can be improved through reading activities and their reading skills can develop well by always growing literacy in students.